Exploring the Relationship Between English Proficiency and Internship Performance for Vocational Students - Wirda Ningsih (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2025)
The growing significance of English in the service industry requires vocational graduates to have not only hospitality technical competence but also English communication skill. This study investigates the relationship between English proficiency which is measured using TOEIC score and students’ internship performance especially those working on hospitality industry. It involves students in the English department at Politeknik Negeri Sriwijaya who have taken their internship in several hospitality industries including hotels, airport, and train stations. English proficiency was measured using TOEIC placement test prior to the internship. Moreover, students’ performance during the internship program was evaluated by their direct supervisors using standardized assessment provided by English Department. The result of data analysis shows that there is a moderate positive correlation (r = 0,54, p < 0,01) between students’ English proficiency and their internship performance. These results suggest that TOEIC scores may be used as a basis for creating focused language help as well as a placement indication. Additionally, they emphasize how crucial task-based and role-specific English learning is for vocational education.